Curtailing Carbon Usage with Addition of Functionalized NiFe2O4 Quantum Dots: Toward More Practical S Cathodes for Li–S Cells - Li, Ning; Meng, Ting; Ma, Lai; Zhang, Han; Yao, JiaJia; Xu, Maowen; Li, Chang Ming; Jiang, Jian (Nano-Micro Letters, 2020)
Smart combination of manifold carbonaceous materials with admirable functionalities (like full of pores/functional groups, high specific surface area) is still a mainstream/preferential way to address knotty issues of polysulfides dissolution/shuttling and poor electrical conductivity for S-based cathodes. However, extensive use of conductive carbon fillers in cell designs/technology would induce electrolytic overconsumption and thereby shelve high-energy-density promise of Li–S cells. To cut down carbon usage, we propose the incorporation of multi-functionalized NiFe2O4 quantum dots (QDs) as affordable additive substitutes. The total carbon content can be greatly curtailed from 26% (in traditional S/C cathodes) to a low/commercial mass ratio (~ 5%). Particularly, note that NiFe2O4 QDs additives own superb chemisorption interactions with soluble Li2Sn molecules and proper catalytic features facilitating polysulfide phase conversions and can also strengthen charge-transfer capability/redox kinetics of overall cathode systems. Benefiting from these intrinsic properties, such hybrid cathodes demonstrate prominent rate behaviors (decent capacity retention with ~ 526 mAh g−1 even at 5 A g−1) and stable cyclic performance in LiNO3-free electrolytes (only ~ 0.08% capacity decay per cycle in 500 cycles at 0.2 A g−1). This work may arouse tremendous research interest in seeking other alternative QDs and offer an economical/more applicable methodology to construct low-carbon-content electrodes for practical usage. Highlights 1 Using NiFe2O4 quantum dots (QDs) as additive substitutes, the total carbon content in cathodes is sharply reduced from original ~ 26% (in traditional S/C cathodes) to a low mass ratio of ~ 5%. 2 The as-built S@CB ⊆ QDs demonstrate more appropriate tap density (~1.32 g cm−3) and specific surface area (~19.9 m2 g−1) values than S@CB counterparts. 3 NiFe2O4 QDs additives possess superb chemisorption interactions with Li2Sn molecules and proper charge-transfer/catalytic features to strengthen redox kinetics of overall cathode systems.